Morphological characteristics, trichomes, and phytochemistry of inflorescences of Humulus lupulus L: Comparison of cropping systems and varieties - Campos, Olivia Pak [UNESP]; Leme, Flávia Maria; Fortuna, Gabriel Cássia [UNESP]; de Oliveira Gomes, Jordany Aparecida [UNESP]; Neves, Caio Scardini [UNESP]; do Carmo de Oliveira Arruda, Rosani; Bonfim, Filipe Pereira Giardini [UNESP] (Southern Cross Publishing, 2023)
This study aimed to assess the influence of cropping systems (conventional and organic) and hops varieties ('Cascade', 'Chinook', 'Columbus', 'Hallertau Mittelfrüh', and 'Nugget') on morphological and anatomical aspects, as well as the contents of essential oil and phenolic compounds of hops inflorescences. Thus, morphological description and cone length; identification of trichomes and peltate glandular trichome density; anatomical and histochemical analysis of peltate glandular trichomes; essential oil content; and total phenolic compound content were evaluated. The results showed no influence of treatments on morphology; however, higher cone lengths were observed in organic cropping and in ‘Cascade’ and ‘Chinook’. These results report the first record of hops trichomes grown in Brazil. Three types of trichomes were identified in inflorescences: nonglandular, peltate, and bulbous glandular. An intense presence of peltate trichomes was observed on flowers. The trichome density in bracts differed among varieties, and 'Cascade' had the highest mean (8.19). There was a significant interaction between cropping systems and varieties for trichome density in flowers: with the exception of 'Nugget' (59.50), the varieties had higher means under organic cropping, especially 'Hallertau Mittelfrüh' (92.12) and 'Chinook' (88.12). Histochemical analysis revealed the presence of polysaccharides, starch, lipids, phenolic compounds, and proteins in peltate trichomes. The cropping systems did not affect the oil content, although there were significant differences between varieties. 'Hallertau Mittelfrüh' showed the lowest oil content (0.25%). Phenolic compounds showed no effect of treatments. Therefore, the results indicate that organic cropping and the 'Cascade' and 'Chinook' varieties are more promising under the conditions studied.
Keywords: Essential oil; Glandular trichome micromorphology; Hops; Lupulin glands; Phenolic compounds; Scanning electron microscopy (SEM)